UPAYA MENINGKATKAN PENJUALAN PADA TOKO TUPPERWARE KECAMATAN SINTANG KABUPATEN SINTANG - Darmansah; Evy Ratnasari; Imam Asrori (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study aims to analyze efforts to increase sales at the Tupperware Store in Sintang District, Sintang Regency. The rapid development of the business world has encouraged companies, including household plastic product retailers, to continuously improve their marketing strategies in order to remain competitive. This research uses a qualitative descriptive approach to understand sales improvement efforts through service quality, business capital management, and the use of social media as a marketing tool. Data were collected through interviews, observations, and documentation involving store owners, employees, and customers. The results show that service quality plays an important role in creating customer satisfaction and loyalty, although employee understanding of promotional details still needs improvement. Business capital management using own capital provides flexibility in operations and stock availability, but stock shortages still occur during certain periods. Social media marketing through Instagram and Facebook has proven effective in increasing brand awareness and customer engagement, although competition with large online stores remains a challenge. Overall, improving employee training, optimizing stock management, and strengthening digital marketing strategies are key factors in increasing sales at the Tupperware Store in Sintang District.